Structures, biological activities, and industrial applications of the polysaccharides from Hericium erinaceus (Lion’s Mane) mushroom: A review - He, Xirui; Wang, Xiaoxiao; Fang, Jiacheng; Chang, Yu; Ning, Ning; Guo, Hao; Huang, Linhong; Huang, Xiaoqiang; Zhao, Zefeng (International journal of biological macromolecules, 2017)
•H. erinaceus is a well-known edible and medicinal higher fungi.•Submerged culture is a good strategy to increase the biosynthesis of H. erinaceus polysaccharides.•Most of H. erinaceus polysaccharides are heteropolysaccharides.•Bioactivities of H. erinaceus polysaccharides are the subject of many recent studies.•H. erinaceus polysaccharides have wide prospects of industrial application. Hericium erinaceus (Bull.) Pers., also known as Yamabushitake, Houtou and Lion’s Mane, is capable of fortifying the spleen and nourishing the stomach, tranquilizing the mind, and fighting cancer. Over the past decade, it has been demonstrated that H. erinaceus polysaccharides possess various promising bioactivities, including antitumor and immunomodulation, anti-gastric ulcer, neuroprotection and neuroregeneration, anti-oxidation and hepatoprotection, anti-hyperlipidemia, anti-hyperglycemia, anti-fatigue and anti-aging. The purpose of the present review is to provide systematically reorganized information on extraction and purification, structure characteristics, biological activities, and industrial applications of H. erinaceus polysaccharides to support their therapeutic potentials and sanitarian functions.